Applied E-Learning of Kolintang Musical Instruments Case Study: University of De La Salle Manado - Liza Wikarsa; Debby Paseru; Vianry Teguh Pangemanan (Widya Teknik, 2016)
Kolintang (Indonesian’s xylophones) is popular nationwide as the traditional music instruments from Minahasa, a regency in North Sulawesi. It is usually played in ancestor worshipping rituals as it was believed that Kolintang had a close relationship with the traditional belief of North Sulawesi's natives and as their culture. Currently, there are several Kolintang applications developed that run either on Windows or Android operating system. They also use different types of controllers like a web camera, touch screen, and keyboard. Unfortunately, these applications are mostly intended for advanced users who have knowledge and skills in playing the Kolintang instruments. In addition, there remains a general lack of research on how to play the five instruments of Kolintang. Thus, this research will develop an e-learning application for the Kolintang musical instruments that are best suited the needs of novice and advanced users. An evaluation framework is developed to assess the quality and efficiency of learning objects of this application on the selected users by incorporating the Unified Theory of Acceptance and Use of Technology (UTAUT). Four criteria identified in this framework that are learning goal alignment, presentation design, interaction usability, and accessibility. The findings revealed that this e-learning application can help both novice and advance users to play the five instruments of Kolintang with ease and smoothness. The learning process can be done at the individual’s choice of pace and time. Key words: E-learning, Kolintang, Multimedia, North Sulawesi